Determination of concentric and eccentric peak moment values for trunk flexion and extension in sedentary asymptomatic individuals by isokinetic dynamometry: a pilot study - Bernardelli, Rafaella Stradiotto (2017)
The spine has a direct influence on postural alignment and movement of the whole body. Lumbar muscles constitute a critical element in trunk performance while weakness of these muscles has been associated with low back pain. Hence, strength profiling of trunk muscles is clinically significant. The objective of this research was to determine, by means of isokinetic dynamometry, peak moment (PM) values during isokinetic concentric and eccentric efforts of trunk flexion and extension in sedentary asymptomatic individuals. The sample consisted of 100 asymptomatic sedentary volunteers, fifty from each sex, aging 22.2 ± 3.3 years old. The sample underwent concentric and eccentric isokinetic assessment of the trunk flexor and extensor muscles at an angular velocity of 60 degrees/sec for each mode of contraction. The mean concentric PM for trunk flexion and extension were 139.5 and 166.6 Nm, respectively, while the respective values for the eccentric efforts were 188.8 and 221.2 Nm. The PM flexion/extension ratio was 0.87 and 0.89 for the concentric and eccentric efforts, respectively. These values of concentric and eccentric PM and PM ratio will serve as comparison parameters for future research, as well as for the assessment of symptomatic patients, and to help in the creation of the trunk muscle rebalance protocols.